2020
DOI: 10.2320/matertrans.mt-m2020133
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of White Band (WB) Formation due to Rolling Contact Fatigue in Carburized SAE4320 Steel

Abstract: We investigated the microstructural changes in carburized steel due to high stress rolling contact fatigue (RCF) in this study. The changes consisted of the formation of white bands (WBs), including the low angle bands (LABs) and high angle bands (HABs), following the formation of a dark etching area (DEA) in the bearing steels below the contact surface. Although several studies have analyzed the characteristics of WBs, their formation mechanism has not been sufficiently elucidated. We analyzed the orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…2(b), although there is no change in the cementite. This result is the same as previously reported; 49) however, the fine, elongated structure corresponding to white bands (WB) as confirmed in the previous report were not observed because different sections of the material were observed. Moreover, the reduction in retained austenite due to RCF was similar to the that observed by X-ray diffraction in previous research.…”
Section: Microstructural Analysis and Crystal Orientationsupporting
confidence: 92%
See 2 more Smart Citations
“…2(b), although there is no change in the cementite. This result is the same as previously reported; 49) however, the fine, elongated structure corresponding to white bands (WB) as confirmed in the previous report were not observed because different sections of the material were observed. Moreover, the reduction in retained austenite due to RCF was similar to the that observed by X-ray diffraction in previous research.…”
Section: Microstructural Analysis and Crystal Orientationsupporting
confidence: 92%
“…During rolling contact, principal shear stress is the highest at a particular depth from the rolling contact surface. 49) Using the Herzian contact theory, the principal shear stress at depth z 0 , at which we conducted the microstructural analyses, is determined to be approximately 1 807 MPa. Additionally, since no known mean critical resolved shear stress (τ CRSS ) is available for austenite in SAE4320 steel or equivalent steels, we used yield stress (σ Y ) of austenite for Fe-Si-Mn-C alloy as reported by Jacques et al, 53) who showed that the σ Y of austenite increases as carbon content increases.…”
Section: Crystal Orientation Relationship Between Parent Austenite and Deformation-induced Martensitementioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Microstructural alterations of the matrix beneath the surface have been considered as important causes of RCF without friction under oil lubrication. Such alterations may be a dark etching area (DEA), 12,13 dark etching constituent (DEC), 12 dark etching region (DER), 12,14 and martensite transformation from retained austenite, 13 which occur in high-stress regions under the ball track. As the number of fatigue cycles increases, characteristic microstructures appear, such as the white band (WB), 12,13 which is type a of shear band, the white etching band (WEB), 12,14 white etching area (WEA), 12,[15][16][17][18][19] white etching cracks (WEC), 14,16 brown etching layer (BEL), 15 and butterfly cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Such alterations may be a dark etching area (DEA), 12,13 dark etching constituent (DEC), 12 dark etching region (DER), 12,14 and martensite transformation from retained austenite, 13 which occur in high-stress regions under the ball track. As the number of fatigue cycles increases, characteristic microstructures appear, such as the white band (WB), 12,13 which is type a of shear band, the white etching band (WEB), 12,14 white etching area (WEA), 12,[15][16][17][18][19] white etching cracks (WEC), 14,16 brown etching layer (BEL), 15 and butterfly cracks. 17 The WEA was found to be composed of ultrafine nanocrystalline ferrite grains, voids, and spherical carbides, as observed by transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%